Enhancing the compost maturation of deer manure and corn straw by supplementation via black liquor. Issue 2 (February 2023) - Pan, Shijun; Wang, Gang; Fan, Yide; Wang, Xiqing; Liu, Juan; Guo, Mingzhu; Chen, Huan; Zhang, Sitong; Chen, Guang
Abstract: In this paper, the relationship between black liquor and microbial growth, enzymatic secretion and humus formation in composting was studied. The results showed that black liquor inoculation is an effective way to promote fermentation process. After black liquor inoculation, the abundance of Corynebacterium, Aequorivita, and Pedobacter, which have the catalase and oxidase activity, has been significantly increased. The enzymatic activity of alkaline phosphatase, catalase, peroxidase and invertase was 40 mg/(g·24h), 6.5 mg/(g·20 min), 13 100 mg/(g·24h), and 6100 mg/(g·24h) respectively at day 18. Humic acid and fulvic acid concentration was 12 g/kg and 11 g/kg which is higher than that of the treatments of no black liquor inoculation. The results suggested that black liquor inoculation was beneficial to indigenous microorganisms reproduce efficiently, then the secretion of enzymes related to cellulose, hemicellulose, and lipid hydrolysis, and the formation of humic substances. Graphical abstract: Image 1 Highlights: The feasibility of using black liquor in compost was proved for the first time. Black liquor promote composting process via activating indigenous microorganisms. Established an operational framework of black liquor/microbial inoculation compost.